Paul as Missionary : Identity, Activity, Theology and Practice. - Burke, Trevor J. (Library of New Testament studies., 2011)
Paul as Missionary: Identity, Activity, Theology and Practice takes the view that before anything else Paul must first and foremost be identified as a 'missionary'. Using the entire Pauline corpus the contributors to this volume assess what Paul's correspondence can tell us about how he perceived his role and identity. The work comprises four parts: in section one, Paul's identity as priest, eschatological herald, and missionary-pastor are explored while in part two topics such as the apostle's activity among pagans, his suffering, and Paul's 'missionary message' to the church at Rome are cons.